2014
DOI: 10.1111/asj.12242
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differential selection traces in two Polish cattle breeds

Abstract: Genetic improvement of animals based on artificial selection is leading to changes in the frequency of genes related to desirable production traits. The changes are reflected by the neutral, intergenic single nucleotide polymorphims (SNPs) being in long-range linkage disequilibrium with functional polymorphisms. Genome-wide SNP analysis tools designed for cattle, allow for scanning divergences in allelic frequencies between distinct breeds and thus for identification of genomic regions which were divergently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Identification of hepatic DE genes in divergent cattle breeds that are specialized for either milk or meat production or raised as dual-purpose breeds might also have significant impact to detect signatures of selection for economically important dairy and beef production traits [57], as well as detecting potential genomic regions relevant to milk and beef production, which were in good agreement with known quantitative trait loci (QTLs) or candidate genes [58,59]. A recent study on genome-wide SNP analysis of Polish-HF and Polish-Red cattle identified 19 genomic regions encompassing 55 protein-coding genes and numerous quantitative trait loci, which potentially underlined some of the phenotypic traits [60].…”
Section: Discussionmentioning
confidence: 95%
“…Identification of hepatic DE genes in divergent cattle breeds that are specialized for either milk or meat production or raised as dual-purpose breeds might also have significant impact to detect signatures of selection for economically important dairy and beef production traits [57], as well as detecting potential genomic regions relevant to milk and beef production, which were in good agreement with known quantitative trait loci (QTLs) or candidate genes [58,59]. A recent study on genome-wide SNP analysis of Polish-HF and Polish-Red cattle identified 19 genomic regions encompassing 55 protein-coding genes and numerous quantitative trait loci, which potentially underlined some of the phenotypic traits [60].…”
Section: Discussionmentioning
confidence: 95%